Plant food processing tools at early Neolithic Göbekli Tepe - Dietrich, Laura (2021)
This volume reconstructs plant food processing at this key Pre-Pottery Neolithic (9600-8000 BC) site, with an emphasis on cereals, legumes and herbs as food sources, on grinding and pounding tools for their processing, and on the vessels implied in the consumption of meals and beverages. Functional investigations on grinding and pounding tools and on stone containers through use-wear and residue analyses are at the core of the book.